Surface morphology characteristics of titanium oxide thin films prepared by spin coating of sol-gel method / Siti Hajar Ismail - Ismail, Siti Hajar (2007)
Titanium dioxide (TiO2) thin films were prepared through hydrolysis and condensation of titanium (IV) isopropoxide, 2-propanol, acetic acid, triton X-100 and deionised water. From this solution it will form into colloidal solution. This is known as sol-gel method and the solution was deposited into silicon substrate using spin coating technique. Sol- gel process is a convenience and inexpensive technique for the production of oxide films of a variety of metals. Spin coating is widely and simple technique whish is widely used for producing a very thin organic films. To form titanium dioxide thin films the solution was dropped and dried repeated for 5 times, to get a certain thickness of thin films. The substrate were anneal at 400°C and 500°C to produce a crystalline structure of TiO2. The surface morphology characteristics of TiO2 thin films was observed using Scanning Electron Microscope (SEM). From SEM, the result showed that the grain boundary of TiO2 thin films was affected by annealing temperature.